Enhancing Students’ Understanding of Simple Past Tense through Website Easy World of English - Dwi Sulistyorini; Haryani; Atria Maharani; Priyanto (JURNAL TRANSMA, 2025)
The use of information technology is currently widely used in various activities with the aim of speeding up work processes and providing significant work effectiveness. Likewise with the process clearance in/out ships which are an important part in the smooth running of port operational activities. This research aims to analyze the effectiveness of using the Indonesia National Single Window (INSW) and Inaportnet system in supporting the process clearance in/out ship at PT. Samudera Agencies Indonesia Surabaya Branch. The research method used is a qualitative descriptive method with data collection techniques through observation and in-depth interviews with five internal sources who have a direct role in the process. clearance boat. The research results show that the implementation of the INSW and Inaportnet systems has a positive influence on accelerating the administrative process, increasing document transparency, and coordinating efficiency between agencies. INSW and Inaportnet systems make a positive contribution in increasing process effectiveness clearance in/out ships through accelerated services and digital document integration. However, this effectiveness still faces obstacles in the form of technical problems, limited infrastructure, and a lack of understanding and training for system users.